Design and development of trivalent aluminum ions induced self-healing polyacrylic acid novel hydrogels. (22nd September 2017) - Anjum, Sadiya; Gurave, Pramod; Badiger, Manohar V.; Torris, Arun; Tiwari, Neha; Gupta, Bhuvanesh
Abstract: Development of ionically crosslinked superabsorbent polyacrylic acid (PAA) self-healing hydrogels using trivalent aluminum ions was investigated. The PAA hydrogels exhibited excellent self-healing behavior depending on the amount of the aluminum within the matrix. The migration of these ions within the polymer matrix was responsible for the physical crosslinking of the hydrogel and the origin of self-healing ability. The PAA-Al hydrogels were insoluble in water and exhibited significantly high degree of swelling (∼4000%). Hydrogel also exhibited good mechanical properties with high level of elongation. Excellent self-healing efficiency was observed under dynamic as well as oscillatory rheological measurements. The presence of Al ions within PAA hydrogel facilitated the self-healing ability because of the ionic interaction in these gels which plays the key role of dynamic reversible sacrificial bonds which reforms upon reversal of the deformative force. Graphical abstract: Highlights: PAA with trivalent Al ions based self-healing hydrogel was developed. Trivalent Al ions acts as physical crosslinker for gel, provide dimensional stability. Free Al ions are responsible for the excellent self-healing property. Hydrogels show excellent self-healing ability along with good mechanical properties.